Perspectives of occupational therapists on the implementation of client-centred practice in Tanzania - Mshanga, Dominick Michael (Department of Health and Rehabilitation Sciences, 2016)
Background: The concept of client-centred practice (CCP) was first developed and implemented by occupational therapists in Canada during the early 1980s and subsequently transferred into the Tanzanian occupational therapy curriculum by international volunteer educators. Currently, the occupational therapy curriculum at the Kilimanjaro Christian Medical University College (KCMUCo) in Moshi, Tanzania covers CCP using assessment tools and models developed by the Canadian Association of Occupational Therapy. To date, no occupational therapy research has been conducted to investigate the relevance of CCP for Tanzania, or to document the perspectives of therapists in applying the principles of CCP. This study was indicated to inform the occupational therapy curriculum at the KCMUCo and the Tanzania Occupational Therapy Association (TOTA) about occupational therapy practice realities related to the implementation of CCP in Tanzania and to guide the alignment of the occupational therapy curriculum towards a local understanding of CCP or an alternative (non-Western) perspective. This study, therefore, aimed to determine the understanding and use of CCP by occupational therapists in Tanzania. Methodology: The study used a descriptive cross-sectional design. All qualified occupational therapists working in different regions in Tanzania were approached to participate in the study (N=80). A questionnaire, the Professional Questionnaire for Assessing CCP (PQACCP) was adapted for the study. The questionnaire consisted of five sections: 1) demographic and practice information; 2) an adaptation of an existing checklist on understanding CCP (Parker, 2006); 3) potential barriers to CCP; 4) enablers of CCP; and, 5) therapist opinions on the relevance of CCP for the Tanzanian context. The checklist of potential barriers and enablers was adapted from Sumsion & Smyth, (2000). Data were analysed using the SSPS software program (version 20.0). Numerical variables were checked for normality and the appropriate measures of central tendency and dispersion calculated. Frequencies and proportions were determined for categorical items. The Chi-square test of association was done to determine whether there were any observed associations between demographic variables and barriers/enablers.